Thoracoscopy-guided thoracic paravertebral block using dexmedetomidine in combination with ropivacaine for postoperative analgesia after thoracoscopic radical resection of lung cancer: a randomized controlled trial - Ke-wei Wu; Shu-yu Deng; Xu-feng Zhang; Da-wei Zheng; Li-hong Hu (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose The aim of this trial was to evaluate the analgesic effect of dexmedetomidine combined with ropivacaine for thoracoscopic-guided thoracic paravertebral block (TTPB) after thoracoscopic radical resection (TRR) of lung cancer. Methods A total of 60 patients were enrolled from our hospital who underwent elective TRR of lung cancer and randomized into either a control group (group C) or a dexmedetomidine group (group D). Prior to incisional suturing, group C received ropivacaine alone for TTPB, while group D received dexmedetomidine combined with ropivacaine for TTPB. The primary outcome was the time to the first analgesic request (TFAR). The secondary outcomes included heart rate (HR), mean arterial pressure (MAP), Ramsay sedation score, and Numerical Rating Scale (NRS) scores (both at rest and during coughing) at the following time points: before the TTPB operation (T0), 1 h postoperatively (T1), 2 h postoperatively (T2), 6 h postoperatively (T3), 12 h postoperatively (T4), 24 h postoperatively (T5), as well as 48 h postoperatively (T6). Additional secondary outcomes included the patient-controlled intravenous analgesia (PCIA) sufentanil dosage at 48 h postoperatively, the incidence of adverse reactions, and postoperative recovery. Results Compared to group C, group D showed a longer TFAR, lower total PCIA sufentanil dosage at 48 h postoperatively, and lower NRS scores at all time points; Group D also had lower MAP and HR, higher Ramsay sedation scores from T1 to T3 after surgery, a higher incidence of drowsiness, and better postoperative recovery. Conclusions As an adjuvant in combination with ropivacaine, dexmedetomidine enhanced the analgesic effect of TTPB, prolonged the duration of analgesia, and reduced the time to first ambulation and hospital stay. Clinical Trial Registration ChiCTR2400086347, Registered 28/06/2024.